Complete Response to Immunotherapy Combined With Chemotherapy in a Patient With Gynecological Mixed Cancer Mainly Composed of Small Cell Neuroendocrine Carcinoma With High Tumor Mutational Burden: A Case Report - Su, Xingyun; Zhou, Xinhui; Xiao, Cheng; Peng, Wei; Wang, Qiangfeng; Zheng, Yulong (Frontiers in Oncology, 2022)
Small cell neuroendocrine carcinoma (SCNEC) is rare in the gynecologic tract, which has high invasive and metastatic ability. Due to the aggressive behavior and lack of treatment, patients have an extremely poor prognosis. Here we report a 66-year-old female diagnosed with SCNEC in the gynecologic tract, mixed with endometrioid adenocarcinoma, squamous cell, and adenosquamous carcinoma. A tumor mutational burden of 13.14 Muts/Mb was detected by next-generation sequencing. The patient underwent a palliative operation of total hysterectomy with bilateral adnexectomy but suffered from disease progression in a short time after the operation. Chemotherapy (paclitaxel + carboplatin) combined with immunotherapy (toripalimab) was conducted every 3 weeks, achieving a partial response after 2 cycles of treatment. After 5 cycles of combined treatment, the patient consolidated with monotherapy of toripalimab for about half a year and achieved a complete response. Until December 2021, the patient has achieved 27 months of progression-free survival and maintains a continued complete response. This case is presented due to the rare combination of pathological types and durable response to treatment especially immunotherapy, suggesting the potential value of immunotherapy in SCNEC of the gynecologic tract.